An Improved Protocol for the Preparation of 5-Substituted Tetrazoles from Organic Thiocyanates and Nitriles - Vorona, Svetlana; Artamonova, Tatiana; Zevatskii, Yuri; Myznikov, Leonid (Synthesis, 2014)
Organic thiocyanates and nitriles are converted efficiently into the corresponding 5-substituted 1H-tetrazoles by treatment with zinc(II) chloride and sodium azide in aliphatic alcohols. The presented procedure provides mild reaction conditions, short reaction times, and good to excellent yields for a wide range of substrates, including deactivated aliphatic nitriles and thermally unstable thiocyanates.
Keywords: tetrazoles; nitriles; thiocyanates; cycloaddition; azides; zinc salts